Letter from Henrietta Dora and Matthias Neumann to Georg Bredig, February 15 1941 - Neumann, Dora; Neumann, Matthias (1941)
Henrietta Dora and Matthias Neumann, friends of the Bredig family, provide updates on their difficult circumstances in the Gurs concentration camp and thank Georg Bredig (1868-1944) and Max Bredig (1902-1977) for sending them provisions.
Keywords: Gurs (Concentration camp); Bredig, Georg, 1868-1944; Nazi concentration camps; Jewish Holocaust (1939-1945)